2003
DOI: 10.1002/cne.10566
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and cytochemical criteria for the identification and delineation of individual subnuclei within the lateral habenular complex of the rat

Abstract: The lateral habenular complex is part of the habenular nuclei, a distinct structure in the dorsal diencephalon of all vertebrates. In contrast to the bewildering diversity of behaviors, in which the lateral habenular complex is thought to be involved, there is an astonishing lack of information concerning its cellular organization, its neuronal circuits, and the neurophysiological mechanisms, which may provide the physiological and molecular basis for its diverse biological functions. This problem may be due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
1
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(160 citation statements)
references
References 49 publications
11
143
1
5
Order By: Relevance
“…Functional significance of the long-lasting depolarization of habenular cells As described in the Introduction, based on anatomical circuitry, the habenula is generally divided into three parts: medial nucleus, medial part of the lateral nucleus, and lateral part of the lateral nucleus Nauta, 1977, 1979;Sutherland, 1982;Ellison, 1994; but see Andres at al, 1999;Geisler et al, 2003). The present study and other previous studies showed that the three areas of the habenula exhibit different electrical properties.…”
Section: The Maintenance and Termination Of The Ldapsupporting
confidence: 61%
“…Functional significance of the long-lasting depolarization of habenular cells As described in the Introduction, based on anatomical circuitry, the habenula is generally divided into three parts: medial nucleus, medial part of the lateral nucleus, and lateral part of the lateral nucleus Nauta, 1977, 1979;Sutherland, 1982;Ellison, 1994; but see Andres at al, 1999;Geisler et al, 2003). The present study and other previous studies showed that the three areas of the habenula exhibit different electrical properties.…”
Section: The Maintenance and Termination Of The Ldapsupporting
confidence: 61%
“…Falling between these two extremes were shortened latencies for incorrect responses and for retrieving the food pellet in lesioned animals, which appeared already in the first block of postoperative test sessions and then remained stable. Given that the habenula consists of 15 subnuclei (Andres et al, 1999;Geisler et al, 2003), it is understandable that alterations with different properties exist. Elucidating the circuits involved in these various alterations will clearly require further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with such widespread influences, it is implicated in diverse functions including anxiety (Murphy et al, 1996;Kurumaji et al, 2003), stress (Amat et al, 2001;Sica et al, 2000), analgesia (Cohen and Melzack, 1993), maternal behavior (Corodimas et al, 1993;Felton et al, 1998), sleep (Haun et al, 1992;Valjakka et al, 1998), behavioral flexibility (Thornton and Evans, 1982), reinforcement (Sutherland and Nakajima, 1981), and spatial memory (Lecourtier et al, 2004). The recent description of 15 subnuclei within the habenular complex (Andres et al, 1999;Geisler et al, 2003) should eventually be of great assistance for future research aimed at elucidating the particular circuits that mediate these specific behaviors.…”
Section: Introductionmentioning
confidence: 98%
“…Autoradiograms of brain sections at several levels of these regions demonstrated that [ 125 I]7-OH-PIPAT-specific binding was prominent and restricted to the medial portion of the lateral habenula ( Figure 1a; Table 1). Detailed analysis of autoradiograms at the level of the habenular complex indicated that D 3 receptor expression was restricted to the parvocellular and central subnuclei of the medial division of the lateral habenula, which concentrates the dopamine mesohabenular TH-immunoreactive nerve terminals (Geisler et al, 2003). A distinct, although lower, [ 125 I]7-OH-PIPAT-specific binding was also detected in the medial part of the basolateral amygdala ( Figure 1c; Table 1), thalamus, and lateral hypothalamus (Figure 1a and c; Table 1).…”
Section: Autoradiographic Localization Of [ 125 I]7-oh-pipatbinding Smentioning
confidence: 99%